COLLEGE AND CHARACTER EDUCATION - Masrukhi Masrukhi (Universitas Muhammadiyah Semarang, 2021)
Universities have an important role in character education. The philosophy of education that combines progressivism, constructivism, and humanism is the foundation of educational activities at universities in Indonesia, which frame the development of student character, in addition to intellectual development and kinesthetic skills. Character education has a very important position considering that global life presents new challenges and changes, which require anticipation and adaptation for the younger generation, including students. The stronger the character possessed by a college graduate, the more capable they will be in dealing with the dynamics of change in the new world. Keywords: Higher Education, Character Education, Tapak Suci